Pemberdayaan Masyarakat Tobimeita melalui Inovasi Kupclang untuk Pengolahan Buah Aren menjadi Kolang Kaling - Rosmarlinasiah, Rosmarlinasiah; Pujirahayu, Niken; Uslinawaty, Zakiah; Laksananny, Satya Agustina; Flamin, Alamsyah; Zulkarnain, Zulkarnain; Bana, Sahindomi; Nur, Hafidah; Hadjar, Nurhayati (Pakis Journal Institute, 2025)
Tobimeita Village in Kendari City, Southeast Sulawesi, has abundant sugar palm (Arenga pinnata) resources that remain underutilized. One of the main challenges in processing sugar palm fruit into kolang kaling is the manual peeling method, which is time-consuming and poses a high risk of injury. This community service program aimed to empower local residents through the introduction of a simple, context-based technology called Kupclang—a mechanical peeler designed to improve safety and efficiency. The activities included socialization, hands-on training, product demonstration, and business mentoring. Results showed that Kupclang reduced peeling time from 90 seconds to just 6 seconds per fruit, achieving a work efficiency increase of 93.33%. The innovation also improved product quality and encouraged active participation, especially among women. This initiative contributed to enhancing local value-added production and opened new opportunities for small-scale entrepreneurship. The program recommends replicating Kupclang in other areas with similar agro-resource potential.